2017
DOI: 10.4025/actascitechnol.v39i1.29385
|View full text |Cite
|
Sign up to set email alerts
|

<b>Estimation of tracked vehicle suspension parameters

Abstract: ABSTRACT. This work aims to estimate the suspension stiffness and damping coefficient of a tracked vehicle by using an inverse problem technique based on Particle Swarm Optimization (PSO) and on Random Restricted Window (R2W). The tracked vehicle has ten road wheels. Each road wheel is linked to a passive and independent suspension. A half car model with seven degrees of freedom describes the bounce and pitch dynamics of the chassis and the vertical dynamics of the wheels. Bounce and pitch accelerations are ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…However, these methods may be considered time consuming and laborious. Therefore, many studies have reported methods for estimating the vehicle parameters using indirect techniques based on measurements taken while the vehicle is in motion (Caldeira et al, 2017;Lalthlamuana & Talukdar, 2017;Majjad, 1997). Studies have examined the influence of the suspension damping and other vehicle properties on the measured response in the vehicle and they have been shown to have an effect (Sharma & Sharma, 2018).…”
Section: Developing An Expression For the Contact-point Responsementioning
confidence: 99%
“…However, these methods may be considered time consuming and laborious. Therefore, many studies have reported methods for estimating the vehicle parameters using indirect techniques based on measurements taken while the vehicle is in motion (Caldeira et al, 2017;Lalthlamuana & Talukdar, 2017;Majjad, 1997). Studies have examined the influence of the suspension damping and other vehicle properties on the measured response in the vehicle and they have been shown to have an effect (Sharma & Sharma, 2018).…”
Section: Developing An Expression For the Contact-point Responsementioning
confidence: 99%